2011
DOI: 10.1007/s13181-011-0172-4
|View full text |Cite
|
Sign up to set email alerts
|

Toxicology, Environmental Health, and the “One Health” Concept

Abstract: The One Health concept promotes collaboration among veterinarians, physicians, scientists, and other professions to promote human, animal, and ecosystem health. One Health illustrates the interconnectedness and interdependence of human, animal, and ecosystem health. This concept has traditionally focused on zoonoses that are infectious diseases, not on chemical-or poison-related illnesses in animals and their relationship to the detection and prevention of human illness. The purpose of this article is to descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 8 publications
(6 reference statements)
0
15
0
Order By: Relevance
“…Evidence for feasibility of integration across all 3 sectors of human, animal, and environmental health, however, came from other studies, such as an article detailing how reports of animal illness facilitated investigations of human cases of disease caused by chemical hazards in the indoor environment ( 14 ). Likewise, a recent state-based effort found benefits of working across human, animal, and environmental health sectors for simultaneously tracking risk for rabies and white nose syndrome in bats ( 16 ), and an effort to track Campylobacter infection in poultry found that environmental temperature affected infection risk for broiler flocks and for humans.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence for feasibility of integration across all 3 sectors of human, animal, and environmental health, however, came from other studies, such as an article detailing how reports of animal illness facilitated investigations of human cases of disease caused by chemical hazards in the indoor environment ( 14 ). Likewise, a recent state-based effort found benefits of working across human, animal, and environmental health sectors for simultaneously tracking risk for rabies and white nose syndrome in bats ( 16 ), and an effort to track Campylobacter infection in poultry found that environmental temperature affected infection risk for broiler flocks and for humans.…”
Section: Resultsmentioning
confidence: 99%
“…Since 2001, the Centers for Disease Control and Prevention has collaborated with AAPCC to use NPDS for national public health surveillance of chemical and poison exposures and illness. Surveillance efforts to date have focused primarily on human health threats but animal illness can serve as a sentinel event for human illness [20]. Surveillance methodologies can also be created for animal exposures and illness.…”
Section: Discussionmentioning
confidence: 99%
“…Poison in common is a dose-dependent potential hazard that adversely affects the standard physiological functions and may threaten the life of living beings (Descotes and Vial, 1994;zhu et al, 2017). The manner of livestock poisoning is frequently associated with the environment imposed by human (Balagangatharathilagar, et al, 2006;Lightfoot and Yeager, 2008;Buttke, 2011). Potential sources of xenobiotics that adversely affect animals include contaminated feed, water, air, and soil (Donner et al, 2010).…”
Section: Introductionmentioning
confidence: 99%